The efficacy and safety of Baduanjin exercise as complementary therapy for pain reduction and functional improvement in knee osteoarthritis: A meta-analysis of randomized controlled trials - Ye Tian; Zi-Yuan Liu; Jia-Hao Wang; Jing-Hua Qian (Complementary Therapies in Medicine)
Abstracts: Objectives: To systematically evaluate the efficacy and safety of Baduanjin exercise in patients with knee osteoarthritis through meta-analysis. While Baduanjin exercise, a traditional Chinese exercise therapy, is part of complementary and alternative medicine, its therapeutic value for knee osteoarthritis remains uncertain due to limited supporting evidence. This study seeks to address this gap. Methods: The study protocol has been registered in PROSPERO(CRD42024501559). A systematic review and meta-analysis were conducted by searching six databases up to January 2024 (PubMed, Cochrane Library, EBSCO, Web of Science and CNKI, and Wanfang Medical), including RCTs that assessed Baduanjin exercise for KOA treatment. Two reviewers independently selected studies, extracted data, and assessed risk of bias using the Cochrane Risk of Bias tool (RoB2). Meta-analyses were performed using RevMan version 5.4.1 software. The outcome indicators included the WOMAC knee pain score, stiffness score, and physical function score, as well as the total score and adverse events. For summary results, weighted mean difference (MD) and 95 % confidence intervals (CI) were used. Results: Twelve RCTs involving 846 participants were included. Baduanjin exercise significantly improved WOMAC pain score (MD=-2.59, 95 % CI: −4.20 to −0.97, P = 0.002), stiffness score (MD=-2.42, 95 % CI: −3.75 to - 1.08, P = 0.004), physical function score (MD=-4.42, 95 % CI: −5.67 to −3.17, P < 0.00001), and total score (MD=-11.27, 95 % CI: −14.26 to −8.28, P < 0.00001) compared to controls. Subgroup analyses revealed significant improvements regardless of intervention duration, frequency, or location. No adverse events were reported. However, high heterogeneity and methodological biases were observed. Conclusion: Baduanjin exercise appears to be an effective and safe complementary therapy for improving pain and function in patients with KOA. High-quality RCTs are needed to confirm these findings and explore optimal intervention parameters. Future research should address the identified methodological limitations.